The Influence of Sharia Financial Literacy and Sharia Financial Inclusion on the Sustainability of Small and Medium Enterprises in the Bandung Raya Region - Amailiya, Lya; Edman, Moch; Sumiyati, Sumiyati (Universitas KH. Abdul Chalim Mojokerto, 2024)
This research aims to determine how much influence Islamic financial literacy and Islamic financial inclusion have on the sustainability of small and medium enterprises in the Bandung Raya area. In the context of Sharia finance, a common problem faced by SMEs today is that many SMEs show a lack of knowledge and ability in financial management. Small and medium enterprises (SMEs) often face challenges in obtaining financial support from institutions, limited options in accessing financial services, and a lack of use of technology to increase competitiveness and encourage innovation. As a result, many SMEs face the risk of bankruptcy. Therefore, this research aims to determine the influence of Sharia financial literacy and Sharia financial inclusion on the sustainability of small and medium enterprises in Bandung Raya. The research was conducted using a quantitative approach, the sampling technique used purposive sampling by considering respondents from SMEs in Bandung Raya that had been established for more than one year and were still actively running businesses. The data analysis technique was carried out using Partial Least Square with the Structural Equation Model (PLS-SEM). The test results show that Sharia financial literacy has a positive effect on business sustainability and financial inclusion has a positive effect on business sustainability in Bandung Raya. These findings add to the literature and present implications for stakeholders to initiate programs that support the sustainability of SME businesses.